Lettuce Cultivars for Insect Resistance in Southern Florida - German Sandoya; Huangjun Lu; Alan L. Wright (EDIS)
Lettuce is the most popular ingredient in salads and salad mixes consumed in the United States. Florida's subtropical climate facilitates lettuce production from fall through spring, but the warm and moist conditions are also favorable for insect proliferation and damage. Insect pests cause direct (feeding) and indirect (contamination) damages to the lettuce crop. This manuscript presents data on cultivars and breeding lines with tolerance to some of these pests. Minor Revision; 5 pp.